Diskursus Gender dalam Perspektif Islam : Gender Discourse from an Islamic Perspective - In'am Fuadi Al Idrus (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2011)
In Indonesia, gender is considered a discourse and a movement that is oriented towards the West, which is why many people, especially those from Islamic boarding schools, are allergic to the term gender. However, if we look closely, long before that, the Quran had revealed the true gender relations in Islam that should exist, only that it did not use the term gender. What is clear is that the Quran discusses the social roles of men and women, including that men and women are equal before Allah (egalitarian), the difference being their level of piety, as stated in (Q.S Al-Hujurat/49: 13);